Intermittent pneumatic compression in patients with postmastectomy lymphedema - Chmielewska, Daria Dominika; Stania, Magdalena; Błaszczak, Edward; Kwaśna, Krystyna (Family Medicine & Primary Care Review, 2016)
Background. Postmastectomy lymphedema frequently affecting young patients constitutes a personal, family and social problem. For this reason, primary care physicians often consult both patients and their families. Objectives. The aim of this study was to evaluate the effects of intermittent pneumatic compression (IPC) alone or in combination with exercises on upper limbs circumference and hand function. Material and methods. The study population consisted of 21 patients with breast cancer-related lymphedema. In Group A, the treatment consisted of 20 IPC sessions (45 minutes a day at 60 mm Hg, 5 times weekly) and physical exercises (combination therapy). Group B only received 20 IPC sessions. Prior to and after intermittent pneumatic compression, all patients had arm circumference measurements at 6 sites on the mastectomy side. Hand function was assessed with the Carpal Tunnel Syndrome Functional Status Scale. Results . Both groups exhibited a reduction in upper limb circumferences after the therapy in comparison to the initial values. However, a comparison of percentage circumference changes did not show any advantage of the combination therapy on the magnitude of the edema and hand function. Conclusions . Pneumatic compression is an effective method of reducing upper limb edema in postmastectomy patients. The exercises did not have a significant effect on function of hand.